THE INFLUENCE OF PRINCIPAL LEADERSHIP ON TEACHER MOTIVATION IN PUBLIC PRIMARY SCHOOL 11th TULANG BAWANG TENGAH - Prastyo, Cendy; Tohir, Ahmad; Mashari, Ali (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This study aims to examine the effect of principal leadership on teachers' work motivation. Leadership is an important social process to achieve the common good in society, including in education. Government Regulation No 32 of 2013 stipulates eight education standards, including educator competency standards. This research focuses on how much influence the principal's leadership has on teachers' work motivation at Primary School 11st Tulang Bawang Tengah. This research is a quantitative study using a correlational research design, while the data analysis technique uses normality test and product moment correlation. The results of this study found that the principal's sample on 10 teachers who were sampled obtained an average value of 70, median of 72.625, mode of 72 with a standard deviation of 13.265. While the results of teacher work motivation from the data obtained an average value of 77.8, a median of 77.5, a mode of 74.5, and a standard deviation of 27.72. Testing the product moment correlation rxy = 0.976 is greater than rtabel so it is known that at the 5% significance level = 0.444 and at the 1% significance level = 0.561, Ho is rejected and Ha is accepted.